Interaction Study of Oxygen and Iron-Sulfur Clusters Based on the Density Functional Theory. (24th September 2022) - Gao, Jiancun; Sui, Hongbin; Wu, Siyuan; Zhang, Renyou; Zhang, Mengxin; Cui, Bolun; Chu, Huilin
Abstract : For the petrochemical industry, the spontaneous burning of iron sulfide compounds has been a major issue. In this study, XRD characterization of samples of iron sulfide compounds with spontaneous combustion tendency revealed that amorphous FeS was the primary constituent of the samples. A molecular simulation was used to build an amorphous FeS cluster model, and the density functional theory was used to examine the adsorption and reactivity characteristics of Fe4 S4 clusters with O2 . Different adsorption structures are generated by considering different adsorption sites and the electronic characteristics of each adsorption structure are evaluated. The results show that O2 prefers to adsorb around Fe atoms and has repulsion with S atoms, and the adsorption energy is maximum when two O atoms are co-adsorbed around Fe atoms, which is 198.13 kJ/mol. After adsorption charge, oxygen is in the superoxide state. The calculation of the reaction path divides the reaction process into different stages and considers different reaction routes. A thorough evaluation of the energy barriers and reaction energies of the two exothermic reactions leads to the conclusion that reaction path 1 is the optimal reaction path, and the reaction can release a total of 582.76 kJ/mol of heat. According to calculations, dimeric sulfur S2 must absorb a large part amount of energy in order to conduct the oxidation process. However, because S2 is present in the Fe4 S4 reaction system, it may start the oxidation reaction by absorbing heat from the system and releasing 470.94 kJ/mol of heat. As a result, we conclude that this spontaneous exothermic reaction is a major cause of iron sulfide compounds spontaneous combustion. The thermal oxidation of the dimeric sulfur S2 generated in the reaction system releases heat that aggregates with the heat from the Fe4 S4 cluster's oxidation reaction system, eventually causing spontaneous combustion as a result of the heat's continual buildup. In this study, we explore the reason for the extremely easy oxidation and spontaneous burning of iron sulfide compounds from a microscopic perspective to provide a theoretical foundation for the prevention and control of iron sulfide compound spontaneous combustion in the petrochemical sector.